Os algoritmos das redes sociais como dispositivos de modulação comportamental - Ane Laura Rios Gouvea (2024)
Each interaction, mediated by technological devices present on social media platforms, is an opportunity to map tastes, habits, preferences, information that is used to shape individuals' subjectivity. This research aims to demonstrate, based on the analysis of patents registered by Meta Inc./Facebook Inc., that digital platforms seek to condition user practices and behaviors, through the collection, mining and profiling of users by their algorithms, by which it is possible to anticipate and predict human behavior, manipulating them in your favor. The method chosen was a bibliographical review of the concepts of device and subject, based on the work History of sexuality: the will to know by Michel Foucault. Foucault's concepts of government and governmentality will also be presented, in general terms, from the Security, Territory, Population course. Next, these concepts will be re-read under the aspect of algorithmic governmentality, in accordance with what is defended by Antoinette Rouvroy and Thomas Berns (2015), in the text Algorithmic governmentality and perspectives of emancipation: the disparate as a condition of individuation through relationship?. At the end of this journey, with the purpose of materially highlighting the thesis defended, the patents promulgated by the social network Facebook will be presented, highlighting how algorithms present themselves as devices inserted in a relationship of force sustaining power-knowledge, instituting a new form of govern subjects, which acts through the optimization and direction of behaviors, social relations and human life.